Cross-Industry Heterogeneity in Export Participation: The Role of Scale Economies in R&D - Shon Ferguson (Research Institute of Industrial Economics (IFN), 2012)
This paper shows that the R&D intensity of an industry plays an important role in determining international trade patterns via its eect on scale economies. I first develop a model of trade with heterogeneous firms where firms compete with each other by spending on fixed product development costs such as R&D. The model predicts that a larger share of firms are exporters in industries where R&D is a large component of total costs. The model also predicts that R&D-intense industries are less sensitive to trade costs. I find empirical support for these predictions using firm-level data for Swedish manufacturing industries. The results also highlight the importance of controlling for firm size when measuring the firm extensive margin of exports.
Keywords: F12; L11; O30; 330; International Trade; Trade Costs; Endogenous Sunk Costs